Young Women's Experiences of Violence and Homelessness - Wendt, Sarah (Violence against women, 2025)
This article explores the lived experience of young women navigating and surviving domestic and family violence (DFV) and homelessness. Promoting the voices of young women through in-depth interviews, this article considers their story of violence, abuse, homelessness, and sense of safety. Such stories enable reflection on the ability of services to provide personal, material, emotional, and cultural safety in a way that recognizes the intersecting impact of trauma before, during, and after experiences of DFV. We conclude by arguing that providing emotional and cultural safety through the relational aspects of service delivery is essential to developing a strong foundation for young women's futures.